Innovative Contracts, Sound Relationships : Urban Water Sector Reform in Senegal - Brocklehurst, Clarissa (World Bank, Washington, DC, 2014)
In 1995, the Government of Senegal launched wide-reaching reforms in the urban water sector. The reforms consisted of dissolving the state-run water company and creating a new asset-holding company that owned all the fixed assets in the government's name and had a mandate to manage the sector. The distribution and production was delegated to a separate entity, and a private operator was engaged to run the system. Eight years later, these reforms have resulted in significantly better services and financial health for the sector. There has been a 20 percent increase in the amount of water supplied, and the number of customers connected has increased by 35 percent. Consumers experience better service delivery in terms of response time to complaints, hours of service, and water quality. The utility is better run, with lower water losses and higher bill recovery. Both the private operating company and the state asset-holding company are healthy organizations, and their working relationship is good.